Composición química y degradabilidad ruminal in situ de ensilajes de cuatro hibridos de maiz forrajero (zea mays l.) En dos edades de cosecha. - Sánchez Ganchozo, Cristhian Oliver (2016)
The research aimed to evaluate the chemical composition and ruminal degradability in situ dry matter (DISMS), organic matter (ism) and inorganic matter (reduc) of silages of four hybrids of forage maize (INDIA S-810, PIONNER 3041, PIONNER 30K73 and INDIA S-505) in two harvest ages (60 and 75 days) Design was used completely randomized (DCA) factorial arrangement 4x2 for the first experiment (CQ) and a complete block design at random (DBCA) in accordance with 4x2 factorial experiment for the second (DIS). The results indicate that in the first experiment chemical composition (CQ) silage hybrids India S-810 at 60 and 75 days old and Pionner 30k73 60 days old vintage had the highest mineral content and silage corn India S-505 60 days obtained the highest percentages of protein (PB), for fiber fractions (NDF) and (FDA) determined that their behavior is directly proportional to the age of the plant when cut , since more older is the fiber content of silage. In the second experiment DISMS of corn silage determined India S-505 to 75 days of harvest obtained the highest percentages of degradability. In the ism at 6 hours of degradability, silage hybrid India S-505 cut at 75 days of regrowth, was the best evaluated treatment, while for the other periods of incubation no significant differences between treatments evaluated were evident.In the reduc at 3 hours of incubation the T6 treatment obtained the highest percentages of ruminal degradability, and for 12 hours the T7 treatments and T8 showed the highest percentages while for the following periods of incubation, no significant differences were observed between the treatments evaluated.